0.07z=-0.72-5(0.3z-1.4)

Simple and best practice solution for 0.07z=-0.72-5(0.3z-1.4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.07z=-0.72-5(0.3z-1.4) equation:


Simplifying
0.07z = -0.72 + -5(0.3z + -1.4)

Reorder the terms:
0.07z = -0.72 + -5(-1.4 + 0.3z)
0.07z = -0.72 + (-1.4 * -5 + 0.3z * -5)
0.07z = -0.72 + (7 + -1.5z)

Combine like terms: -0.72 + 7 = 6.28
0.07z = 6.28 + -1.5z

Solving
0.07z = 6.28 + -1.5z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '1.5z' to each side of the equation.
0.07z + 1.5z = 6.28 + -1.5z + 1.5z

Combine like terms: 0.07z + 1.5z = 1.57z
1.57z = 6.28 + -1.5z + 1.5z

Combine like terms: -1.5z + 1.5z = 0.0
1.57z = 6.28 + 0.0
1.57z = 6.28

Divide each side by '1.57'.
z = 4

Simplifying
z = 4

See similar equations:

| m/7-9=8 | | 9a+12=7a+9 | | 0-y=111 | | 250+t=141 | | 56ty-11=247 | | 200-3y-4x=0 | | 8.1-0.6t=7.2 | | 7(2x+10)=6x+26+6x+4 | | a-95=25 | | gcf=42x+28y | | b-5+0.2b=-0.2 | | -8(7)+y=4 | | x^5-3x^4-x^3+3x^2=f(x) | | 2/3+3x+1/4=5/3 | | -8(3)+y=4 | | 3.2x-0.88+1.2=0 | | -8(-2)+y=4 | | 2(5x+4)+2=60 | | 4g-8=-20 | | X*2+5x+3=0 | | 2+3(5+5v)=62 | | 42x+28y=gcf | | -2(3y-4)-y=-4(y-2) | | 3(3x+2)=6(2x-3) | | 9x+3=7x-19 | | 2+15+15v=62 | | 40r^2-35r+16r-14=0 | | 50m+42750=42675-175m | | 4(2x-7)=3(x-1) | | 5y+35=x+5 | | G(10)=50 | | 7x-47=x |

Equations solver categories